Handwashing Results in Incomplete Nicotine Removal from Fingers of Individuals who Smoke: A Randomized Controlled Experiment - Northrup, Thomas F.; Stotts, Angela L.; Suchting, Robert; Khan, Amir M.; Klawans, Michelle R.; Green, Charles; Hoh, Eunha; Hovell, Melbourne F.; Matt, Georg E.; Quintana, Penelope J. E. (American Journal of Perinatology, 2021)
Objective Tobacco residue, also known as third-hand smoke (THS), contains toxicants and lingers in dust and on surfaces and clothes. THS also remains on hands of individuals who smoke, with potential transfer to infants during visitation while infants are hospitalized in neonatal intensive care units (NICUs), raising concerns (e.g., hindered respiratory development) for vulnerable infants. Previously unexplored, this study tested handwashing (HW) and sanitization efficacy for finger-nicotine removal in a sample of adults who smoked and were visiting infants in an NICU.Study Design A cross-sectional sample was recruited to complete an interview, carbon monoxide breath samples, and three nicotine wipes of separate fingers (thumb, index, and middle). Eligible participants (n = 14) reported current smoking (verified with breath samples) and were randomly assigned to 30 seconds of HW (n = 7) or alcohol-based sanitization (n = 7), with the order of finger wipes both counterbalanced and randomly assigned. After randomization, the first finger was wiped for nicotine. Participants then washed or sanitized their hands and finger two was wiped 5 minutes later. An interview assessing tobacco/nicotine use and exposure was then administered, followed by a second breath sample and the final finger wipe (40–60 minutes after washing/sanitizing).Results Generalized linear mixed models found that HW was more effective than sanitizer for nicotine removal but failed to completely remove nicotine.Conclusions Without proper protections (e.g., wearing gloves and gowns), NICU visitors who smoke may inadvertently expose infants to THS. Research on cleaning protocols are needed to protect vulnerable medical populations from THS and associated risks.Key Points
Keywords: thirdhand smoke; THS; neonatal ICU; THS removal; handwashing; sanitizer